Analysis of Cadmium (Cd) Heavy Metal Levels in Groundwater around Lapindo Mudflow, Sidoarjo Regency - Ulumiya, Nova; Kunsah, Baterun; Kartikorini, Nastiti; Mardiyah, Siti (Mukhtabar Journal of Medical Laboratory Technology, 2024)
Background & Objective: Metal pollution in Lapindo mudflow is one of the events that cause pollution because the content in the mud contains a variety of heavy metals, one of which is cadmium (Cd). Cadmium is a heavy metal that has high toxicity and is included in non-essential heavy metals, so the presence of heavy metal cadmium (Cd) needs to be known for sure because too high levels can harm health and the surrounding environment. The purpose of this study is to determine the presence of cadmium (Cd) heavy metal levels in groundwater around Lapindo Mudflow, Sidoarjo Regency. Method: This study uses descriptive type and design. The sampling technique used purposive sampling by taking 4 points and conducting a duplo examination so that the total number of samples was 8 samples. Results: The results showed that out of 8 samples, all samples still met the requirements according to SNI with a percentage of 100%. Conclusion: It can be concluded that the results of the study with an average of 0.5075 × 10-4 mg/L still meet the requirements in accordance with the Indonesian National Standard (SNI) which is 0.5 - 10.0 mg/L or 0.0005 - 0.001 mg/L.